Genotype–Phenotype Correlations in Ornithine Transcarbamylase Deficiency: A Mutation Update - Caldovic, Ljubica (J Genet Genomics, 2015)
Ornithine transcarbamylase (OTC) deficiency is an X-linked trait that accounts for nearly half of all inherited disorders of the urea cycle. OTC is one of the enzymes common to both the urea cycle and the bacterial arginine biosynthesis pathway; however, the role of OTC has changed over evolution. For animals with a urea cycle, defects in OTC can trigger hyperammonemic episodes that can lead to brain damage and death. This is the fifth mutation update for human OTC with previous updates reported in 1993, 1995, 2002, and 2006. In the 2006 update, 341 mutations were reported. This current update contains 417 disease-causing mutations, and also is the first report of this series to incorporate information about natural variation of the OTC gene in the general population through examination of publically available genomic data and examination of phenotype/genotype correlations from patients participating in the Urea Cycle Disorders Consortium Longitudinal Study and the first to evaluate the suitability of systematic computational approaches to predict severity of disease associated with different types of OTC mutations.